Modal response and vibration attenuation of carbon fiber composite sandwich cylindrical panels made of bi-directional corrugated strip cores. Issue 2 (10th February 2022) - Li, Shuang; Yang, Jin-Shui; Chen, Si-Yuan; Zhang, Wei-Ming; Schmidt, Rüdiger; Schröder, Kai-Uwe; Yang, Li-Hong; Wu, Lin-Zhi
Abstract: To explore desirable structures with both higher fundamental frequency and better vibration suppression, we designed and fabricated carbon fiber composite bi-directional corrugated sandwich cylindrical panels (BCSCPs) by a hot press molding and post-assembly approach. Modal response and vibration attenuation performance of such structures were investigated experimentally and numerically. Furthermore, the free and forced vibration responses of simple laminated cylindrical panels (SLCPs), axial corrugated sandwich cylindrical panels (ACSCPs) and circular corrugated sandwich cylindrical panels (CCSCPs) with almost the same relative density were investigated and compared with that of BCSCPs. The results indicated that the numerical models were reasonable to estimate the vibration properties of BCSCPs, and the vibration attenuation performance can be improved by suitably increasing the thickness of face sheet and bi-direction corrugated core. Besides, it was revealed that the BCSCPs, ACSCPs and CCSCPs all had comparatively better vibration attenuation performance than that of the SLCPs, and the present BCSCPs generally had higher natural frequencies than those of the ACSCPs and CCSCPs with almost the same weight, which may provide some references for further engineering application of such kinds of composite sandwich structures.